The Effectiveness of Rosella on Blood Pressure in Individuals with Hypertension: A Systematic Review - Longlalerng, Winit; Itharat, Arunporn; Siriwattanasatorn, Metar; Tatong, Thunyaluk (Thammasat University Hospital Journal Online, 2025)
Background: Hypertension is a major cause of stroke and heart disease, leading to death. Currently, many individuals with hypertension seek alternative treatments to help lower blood pressure, with the use of Thai herbs being one such option. Roselle (Hibiscus sabdariffa L.) is a Thai herb listed in the National Essential Medicines List and is known for its potential to lower blood pressure. Objective: To review, analyze, synthesize, and summarize studies on the effects of roselle on blood pressure in patients with hypertension. Materials and methods: The Joanna Briggs Institute methodology included research published between 2013 and 2023. Randomized controlled trials (RCTs) and quasi-experimental studies were selected and examined for the effects of roselle on blood pressure in hypertensive patients, with a total of 7 studies meeting the inclusion criteria. Results: The findings of this systematic review revealed that roselle can lower systolic blood pressure in hypertension patients, although its effect on diastolic blood pressure was inconclusive, it may or may not reduce diastolic pressure. When compared to standard hypertension management, the combination of roselle supplementation with lifestyle changes was found to be more effective at lowering blood pressure than lifestyle changes alone. However, it could not be conclusively stated that roselle is more effective than conventional antihypertensive medications. Conclusion: Roselle influences blood pressure in patients with hypertension, leading to a decrease in blood pressure among those who consume it.